(untitled) (Bangladesh Pharmaceutical Journal, 2018)
This article focuses on the chemical constituents and protection of biodiversity through plantation of saplings of Corypha taliera Roxb., a critically endangered plant of Bangladesh. Until 2010, the tree in the campus of University of Dhaka, used to be considered as the lone surviving species in the world in nature. Succesive chromatographic separation and purification of the methanol extract of air dried flowers of C. taliera provided β-sitosterol (1), β-amyrin (2), and betulinic acid (3) for the first time from its flowers. The structures of these purified compounds were established by extensive spectroscopic analysis and comparison of spectral data with published values as well as co-TLC with authentic samples. On the other hand, 500 mature seeds were sown in seed beds in the Medicinal Plant Garden of Faculty of Pharmacy, University of Dhaka, and Azimpur Government Officers’ Quarter premises. After 40 days, the root was first seen to grow in its habitat and 85 days later the shoot developed up to 2.5 cm in height. The rate of germination was found to be 89-93%. The produced saplings were later on planted in different places of Bangladesh for conservation of the plant and protection of biodiversity by ex situ arrangement. Bangladesh Pharmaceutical Journal 20(2): 213-220, 2017